Koi Herpes Virus (KHV) Disease - Kathleen H. Hartman; Roy P.E. Yanong; B. Denise Petty; Ruth Francis-Floyd; Allen C. Riggs (EDIS)
Koi herpes virus (KHV), a viral disease highly contagious to fish, may cause significant morbidity (sickness or disease) and mortality in common carp (Cyprinus carpio) (Hedrick et al., 2000; OATA, 2001). This species is raised as a foodfish in many countries and has been selectively bred for the ornamental fish industry, where it is known as koi. Historically, the first outbreak of KHV was reported in 1998 and confirmed in 1999 in Israel. Since then, other cases have been confirmed in the United States, Europe and Asia (Hedrick et al., 2000; OATA, 2001; Anonymous, 2003). This information sheet is intended to inform veterinarians, biologists, culturists, and hobbyists about KHV. This document is Fact Sheet VM-149, one of a series from the Department of Large Animal Clinical Sciences (College of Veterinary Medicine), Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: June 2004.